SELFNET 5G mobile edge computing infrastructure: Design and prototyping. (10th February 2019) - Chirivella‐Perez, Enrique; Marco‐Alaez, Ricardo; Hita, Alba; Serrano, Ana; Alcaraz Calero, Jose M.; Wang, Qi; Neves, Pedro M.; Bernini, Giacomo; Koutsopoulos, Konstantinos; Gil Pérez, Manuel; Martínez Pérez, Gregorio; Barros, Maria João; et al.
Summary: This paper presents the design and prototype implementation of the SELFNET fifth‐generation (5G) mobile edge infrastructure. In line with the current and emerging 5G architectural principles, visions, and standards, the proposed infrastructure is established primarily based on a mobile edge computing paradigm. It leverages cloud computing, software‐defined networking, and network function virtualization as core enabling technologies. Several technical solutions and options have been analyzed. As a result, a novel portable 5G infrastructure testbed has been prototyped to enable the preliminary testing of the integrated key technologies and to provide a realistic execution platform for further investigating and evaluating software‐defined networking– and network function virtualization–based application scenarios in 5G networks.